Q: 2m plus 2 equals 3m plus 4?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

-2m + 7 = m - 2 +7 +2 = m +2m 9 = 3m 3m = 9 m = 9/3 = 3 to test: -2(3) + 7 = (3) - 2 -6 + 7 = 3 - 2 1 = 1

-3m + 8 = 2 -3m = 2 - 8 -3m = -6 m = -6/-3 m = 2

5m+3=3m+9 First get the ms and the constants on separate sides. Do this by subtracting 3 from both sides (5m=3m+6) Then subtract 3m from both sides (2m=6) then divide both sides by 2 to find m. (m=3)

M= 2.

(10, 2)

Related questions

5m+3=3m+9 5m+3-3=3m+9-3 5m=3m+6 5m-3m=3m+6-3m 2m=6 (2m)/2=6/2 m=3

m(3m + 2)

-2m + 7 = m - 2 +7 +2 = m +2m 9 = 3m 3m = 9 m = 9/3 = 3 to test: -2(3) + 7 = (3) - 2 -6 + 7 = 3 - 2 1 = 1

-3m + 8 = 2 -3m = 2 - 8 -3m = -6 m = -6/-3 m = 2

5m+3=3m+9 First get the ms and the constants on separate sides. Do this by subtracting 3 from both sides (5m=3m+6) Then subtract 3m from both sides (2m=6) then divide both sides by 2 to find m. (m=3)

3m x 2m = 6 m2

M= 2.

3m+2=17 First, subtract 2 to get m on one side. 3m+2-2=17-2 3m=15 Divide by 3 to get m by itself. 3m/3=15/3 m=5 m equals 5.

(10, 2)

0 = 2m^2 - 2m + 36 0 = 2(m^2 - m + 18) 0 = m^2 - m + 18

That factors to 2m(m + 6)(3m - 2)

13=m+2m=11